A Study Cultural Dimension and local Wisdom for Industrial Crafts Design - Keativipak, Kittipong (Journal of Fine and Applied Arts Khon Kaen University, 2021)
Example of cultural dimension and local wisdom approach concept to industrial crafts design was part of the research on “The design and development of industrial crafts products from the integration of local wisdom for increasing economic values”. The objective is to obtain industrial crafts products from the integrated and application of local wisdom to create a new industrial crafts product in promoted local arts and crafts to have more products and obtained products that can be developed further including cooperated between the communities in the production of works. Research methodology: This research was qualitative and there are 3 main components in this part. First, Studied research data using Individual Depth Interview and focus group methods. Second, Participatory action research methods for design developed, and selected the arts and crafts community groups in Lampang provinces, amount 4 communities by using the Purposive Sampling method. Third, Questionnaires based for evaluated the studied and opinions of 500 people on industrial crafts products. Results: 1) Focus on the development and creation of new products. The concept of creativity is community product development through knowledge and innovation to become an interesting industrial crafts product different from the original product and creating market opportunities.2) Example of cultural dimension and local wisdom approach concept to industrial crafts products from industrial crafts design framework, amount 2 products by using the cultural dimension of Howdah and Lanna art and crafts. 3) Assessing opinions about industrial crafts products by using the cultural dimension and local wisdom approach at the best level (mean = 4.59).